PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN UD TIGA PUTRA DI KABUPATEN BULUKUMBA - Jamnur, Adrian Maulana; Ruma, Zainal; Nurman (Transpublika Publisher, 2022)
This study aims to test whether the variables have an effect on employee performance at UD Tiga Putra. The population in this study is a total of 32 employees of UD Tiga Putra, while the sample in this study using the saturated sample technique will be found 32 people. The data collection technique used is a questionnaire. The data collected is then entered into a simple linear regression equation. The findings in this study indicate that partially the leadership variable has a positive and significant effect on employee performance at UD Tiga Putra in Bulukumba Regency. Hence, every time there is an increase in leadership it will improve employee performance and vice versa. So that the hypothesis in this study is accepted. Based on the results of the study, it can be said that companies need to maintain a leadership strategy by receiving good suggestions, paying attention to employees and not only the company and employee involvement in the company's decision-making process as a step in improving employee performance. In addition, UD Tiga Putra needs to improve on leadership in making decisions that must be carried out absolutely by employees, because this will have an impact on suppressing employees which will make the employee's performance decrease.